THE INFLUENCE OF COMPLEX PREPARATIONS BASED ON HYDROGEL AND CULTURE OF PHOSPHATE-MOBILIZING BACTERIA BACILLUS MYCOIDES A7 ON TOMATO GROWTH UNDER LIGHT CULTURE - Eliseeva, Anna D.; Maksimov, Alexander Yu (Siberian journal of life sciences and agriculture, 2024)
Background. Uneven distribution and lack of water is one of the global problems faced all over the world. Particularly relevant is the uneven water supply for crop production. In agricultural practice, the problem of water shortage can be solved by introducing preparations based on hydrogels into the soil. The use of hydrogels makes it possible to reduce the frequency of irrigation and soil compaction, stop erosion, leaching of nutrients and biogenic elements, optimize soil aeration and microbiological activity. However, agricultural sorption polymers available on the market do not solve the problems of plant nutrition and health improvement. The purpose of these experiments is to determine the effect of complex preparations based on a polymer carrier and a strain of phosphate-mobilizing bacteria Bacillus mycoides A7, which has amylase and lipase activity, on the growth of tomato seedlings under light culture conditions. Materials and research methods. To assess the effect of different variants of the biological product on the growth of tomatoes of the early ripe variety "Balkonnoe chudo", the morphometric parameters and biochemical parameters of plants were measured. In each variant, the mean value and standard deviation were determined. Proline concentration in leaves was measured as described by Bates et al., 1973. Protein concentration was determined by the method of Bradford, 1976. The activity of the antioxidant peroxidase enzyme was evaluated by the method of Chance and Maley, 1955. Catalase activity was measured by the method of Nakano and Asads, 1981. Results. It has been shown that the addition of both Bacillus mycoides A7 biomass and the obtained complex preparations to the soil has a pronounced growth-stimulating effect on model plants. Inoculation of a liquid suspension of B. mycoides A7 culture stimulated the growth of model plants to a greater extent than all preparations of pure hydrogel, but to a lesser extent than all complex preparations of this culture with hydrogels. It was also established that the variants with the introduction of a bacterial culture and a complex preparation contain lower concentrations of stress factors, which indicates the normalization of metabolic processes and the general condition of model plants. Conclusion. The study of the effect of complex preparations based on polyacrylamide hydrogel and a culture of phosphate-mobilizing bacteria Bacillus mycoides A7, a producer of amylase and lipase enzymes, on the growth of tomato plants of the early ripening "Balkonnoe chudo" variety under light culture conditions showed that this culture, as part of a complex preparation, normalizes the physiological hygienic state and stimulates plant growth.